In Search of the Jolly Green Giant: Emerging Ideas about Sustainable Housing - Lawrence Scarpa (Oz, 2003)
Early architects and builders helped humankind survive in a hostile world. In our journey from rudimentary and primitive shelters to an architecture that represents contemporary culture, we are experiencing a paradigm shift in our attitude about the earth.